<p>Could someone help me with:</p>

<p>What is y if ((y-x)^2- (y-z)^2)/(z-x) = y-z? Assume x is not equal to z.</p>

<p>A) z, B) x, C) xz, D) xz-z, E) X^2+z^2-xz</p>

<p>Thanks for your help.</p>

<p>Could someone help me with:</p>

<p>What is y if ((y-x)^2- (y-z)^2)/(z-x) = y-z? Assume x is not equal to z.</p>

<p>A) z, B) x, C) xz, D) xz-z, E) X^2+z^2-xz</p>

<p>Thanks for your help.</p>

<p>Is the answer B?</p>

<p>yes, could you explain how u got that?</p>

<p>There is probably an easier way of solving this problem, but I solved it the long way.</p>

<p>First I multiplied (z-x) on both sides of the equation.

(y-x)^2 - (y-z)^2 = (y-z)(z-x)

Then I multiplied everything out.

y^2 -2xy + x^2 -y^2 +2yz +z^2 = yz -xy -z^2+ xz

Next I added and subtracted terms so that the equation would be simplified

-xy + x^2 + yz = xz

I then subtracted yz from both sides of the equation.

x^2 -xz = xy -yz

Factor out an x on the left side, and a y on the right.

x(x-z) = y(x-z)

Divide both sides by (x-z)

x = y </p>

<p>Again there is probably an easier way to due this, but this works.</p>